2014
DOI: 10.4172/2155-6148.1000477
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of Oncology Nurses towards Complementary and Alternative Medicine for Cancer Care in Qatar

Abstract: Aim and objectives: The aim of this study is to investigate the knowledge, attitudes and practices of oncology nurses towards CAM in cancer care in Qatar. Background: CAM is widely used by patients with cancer worldwide. Given the wide use of CAM in cancer treatment, cancer authorities have called for an increased awareness of CAM modalities among healthcare professionals with a focus on safety and efficacy. Among healthcare professionals, nurses play a vital role in the integration of CAM into cancer care. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(54 reference statements)
1
1
0
Order By: Relevance
“…Nurses’ recommendation of exclusive alternative medicine for NHL patients may deviate from evidence-based practice and compromise standard pharmacotherapy effectiveness. This highlights a lack of basic knowledge regarding alternative medicine among nurses, consistent with a previous study in Qatar emphasizing the need to enhance complementary therapy education for oncology nurses [ 42 ]. On the other hand, Canadian oncology nurses acknowledge the importance of complementary and alternative medicine as part of person-centered care, emphasizing its inclusion in the foundations of oncology nursing practice.…”
Section: Discussionsupporting
confidence: 85%
“…Nurses’ recommendation of exclusive alternative medicine for NHL patients may deviate from evidence-based practice and compromise standard pharmacotherapy effectiveness. This highlights a lack of basic knowledge regarding alternative medicine among nurses, consistent with a previous study in Qatar emphasizing the need to enhance complementary therapy education for oncology nurses [ 42 ]. On the other hand, Canadian oncology nurses acknowledge the importance of complementary and alternative medicine as part of person-centered care, emphasizing its inclusion in the foundations of oncology nursing practice.…”
Section: Discussionsupporting
confidence: 85%
“…Hassan et al (2014) concluded that 88.8% of the nurses had already heard about NCT. 93.5% of those nurses think that NCT can help the patients, 24.3% often recommend these therapies to their patients and 84.9% would inform the institution in which they work about the advantages of introducing these NCT as an essential part in the treatment of oncological diseases.…”
mentioning
confidence: 99%